A case of probable sporadic Creutzfeldt-Jakob disease. Issue 4 (1st December 2017) - Hussein, Norita
Abstract : Creutzfeldt-Jakob Disease (CJD) is a fatal neurodegenerative brain disease. The author describes a case presented to primary care clinic whereby neuropsychiatric symptoms were the patient's initial presentation which later manifested with declining cognitive impairment, myoclonus and extrapyramidal symptoms. A typical abnormal magnetic resonance imaging (MRI) features were observed. The patient succumbed within six months of presentation.